Community and Institutions in Indonesia's Energy Transition: LPG, Biogas, and Clean Cooking for Sustainability - Islamiati, Indri; Andre Lofika Pegi (Kementerian Koordinator Bidang Pembangunan Manusia dan Kebudayaan Republik Indonesia, 2024)
Transitioning to cleaner cooking energy sources like LPG and biogas is essential for achieving sustainable development in rural Indonesia. This study, utilizing data from over 84,000 villages in the 2021 Village Potential Survey (PODES), examines the factors influencing the adoption of these technologies. Adoption in this context refers to the replacement or supplementing of traditional biomass fuels with modern, cleaner energy sources. Logistic regression reveals that inter-village cooperation, women’s empowerment, road access, and the availability of LPG sales points significantly increase the likelihood of LPG adoption. Meanwhile, ordinary least squares (OLS) regression indicates that while inter-village cooperation reduces household biogas expenditure due to shared infrastructure, factors such as women’s empowerment, road access, and institutional support through village cooperatives significantly enhance biogas use. These findings highlight the critical roles of social, institutional, and infrastructural factors in driving clean energy adoption. The study calls for integrated policies to address socio-economic barriers, strengthen local institutions, and promote equitable access to clean energy in rural areas.